The Correlation of Emotional Intelligence and Self-efficacy in Patients with Intestinal Stoma - F Nasiri Ziba; M Saati; H Haghani (Iran University of Medical Sciences, 2019)
Background & Aims: Patients with intestinal stoma experience periods of psychological and physical disorders, including disturbances in self-efficacy. It is presumed that factors such as emotional intelligence could be associated with self-efficacy in these patients. The present study aimed to determine the correlation between emotional intelligence and self-efficacy in patients with intestinal stoma. Materials & Methods: This descriptive-correlational study was conducted on 155 patients (79 men and 76 women) with intestinal stoma (colostomy and ileostomy) referring to the selected hospitals affiliated to Iran University of Medical Sciences and Iranian Ostomy Association in 2018. The patients were selected via convenience sampling. Data were collected using a demographic questionnaire, ostomy self-efficacy questionnaire, and Schutte self-report emotional intelligence test. Data analysis was performed in SPSS version 16 using descriptive and inferential statistics, including the analysis of variance (ANOVA) and independent t-test. Results: The results of Pearson's correlation-coefficient indicated a positive, significant correlation between emotional intelligence and self-efficacy (P<0.001; r=0.49). However, no significant associations were observed between demographic variables and emotional intelligence. On the other hand, self-efficacy was significantly correlated with the marital status of the patients (P=0.03), so that the married patients had higher self-efficacy compared to the single patients. Conclusion: According to the results, the patients with higher emotional intelligence had higher self-efficacy. Therefore, it is recommended that proper planning and educational interventions be implemented regarding emotional intelligence in order to enhance self-efficacy in patients with intestinal stoma.